Compatibilidade e estabilidade do cloridrato de trazodona associado a excipientes farmacêuticos - Menezes, Tarcísio Antônio Dos Reis (2019)
There are several ways of treating depressive disorders, one of which is the treatment with trazodone hydrochloride pharmaceutical formulations, a selective serotonin reuptake inhibitor, which is widely used in the treatment of depression because it is characterized by lower anticholinergic properties when compared to tricyclic antidepressants. Thus, this work has proposed to study the compatibility and stability of trazodone hydrochloride in the presence of the excipients sodium stearyl fumarate, tribasic calcium phosphate, hypromellose, microcrystalline cellulose and lactose monohydrate, since studies of this character have not yet been found in the literature. Possible incompatibilities were analyzed using thermal analysis; TG/DTA/DTG and DSC curves. Binary mixtures in the ratio 1:1 mass/mass were used between the active principle and each of the excipients. By the TG technique, changes in the drug-related decomposition events were observed in the binary mixtures. Since the behavior of the experimental curves differed from the behavior expected by the theoretical curves, especially at temperatures above 200 C. In the DSC analyzes, the parameters defined by ICH were used for the accelerated stability study. All excipients were shown to be incompatible with trazodone hydrochloride, either by overrunning or overturning its characteristic peak Ton-set. In the kinetic study, the influence of the association with sodium stearyl fumarate and with lactose monohydrate was studied in the activation energy related to the first stage of drug decomposition. An increase in Ea was observed when trazodone hydrochloride was associated with 16.05% sodium stearyl fumarate according to the dynamic method and a decrease of 25.33% according to the isothermal method. The divergence between the methods, in the case of this mixture, occurs because the experimental data does not fit a good range of xm for the dynamic method. Already when it was associated with lactose monohydrate the activation energy of trazodone hydrochloride increased by 50.47% in the case of the dynamic kinetic study and 32.99 % in the case of the isothermal kinetic study.